The Variable Emergence of the Infrapatellar Branch of the Saphenous Nerve - Henry, Brandon Michael; Tomaszewski, Krzysztof A.; Pękala, Przemysław A.; Ramakrishnan, Piravin Kumar; Taterra, Dominik; Saganiak, Karolina; Mizia, Ewa; Walocha, Jerzy A. (The Journal of Knee Surgery, 2017)
The infrapatellar branch of the saphenous nerve (IPBSN) is a cutaneous nerve of the lower limb, which arises distal to the adductor canal. High variability in the emergence, course, branching, termination, and morphometrics of the IPBSN poses an increased risk of injury to the nerve during surgical interventions on the anteromedial aspect of the knee. The aim of this study was to describe the anatomical characteristics of the IPBSN. This study utilized cadaveric (n = 100) and ultrasonography (n = 30) assessments, and meta-analysis. In the cadaveric study, the presence of IPBSN and its emergence mode in relation to the sartorius muscle (SaM) was determined (type A-anterior; type B-posterior; type C-penetrating the SaM). Ultrasonography examinations were conducted on healthy volunteers to determine the presence and mode of the emergence of the nerve. Finally, from electronic databases searching, all studies reporting the IPBSN emergence data were pooled into a meta-analysis. The mean distance between the medial border of the patellar ligament (MBPL) and the IPBSN at the level of the patellar apex (PA) was also analyzed in the cadaveric, ultrasonography, and meta-analysis portions of the study. Six studies (n = 336 limbs), including the present cadaveric study, were pooled into the meta-analysis of emergence. The most prevalent IPBSN emergence mode was type C (42.9%) followed by type B (41.9%) and type A (15.4%). In the ultrasonography assessment, type A was found to be the most common (82.8%). The mean distance between the MBPL and the IPBSN at the level of the PA was 4.89 ± 0.22 cm, and 5.57 ± 0.91 cm, for the cadaveric and meta-analysis studies combined, and the ultrasonography assessment, respectively. This multimodality study shows that the most common type of IPBSN emergence is type C. The horizontal distance between the MBPL and the IPBSN at the level of the PA is usually between 4.5 and 5.6 cm. Understanding the anatomy of IPBSN emergence is crucial for orthopedic surgeons to minimize the risks of iatrogenic nerve injury during surgical procedures in the region.
Keywords: infrapatellar branch of the saphenous nerve; anatomy; variation